Estimating demand with multi-homing in two-sided markets - Pauline Luise Affeldt; Elena Argentesi; Lapo Filistrucchi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2021)
We empirically investigate the relevance of multi-homing in two-sided markets. First, we build a micro-founded structural econometric model that encompasses demand for differentiated products and allows for multi-homing on both sides of the market. We then use an original dataset on the Italian daily newspaper market that includes information on double-homing by readers to estimate readers' and advertisers' demand. The results show that an econometric model that does not allow for multihoming is likely to produce biased estimates of demand on both sides of the market. In particular, on the reader side, accounting for multi-homing helps to recognize complementarity between products; on the advertising side, it allows to measure to what extent advertising demand depends on the shares of exclusive and overlapping readers.
Keywords: C51; D43; L13; L82; M37; 330; two-sided markets; platforms; multi-homing; media; advertising